Exploring the subject, adjunct and Wh-island constraints in the usage of English in some selected Nigerian newspapers - Lynda Ambrose; Stela Igene (Universitas Ahmad Dahlan, 2022)
This paper explores the subject, adjunct and Wh-island constraints in the usage of English in some selected Nigerian newspapers. The purpose is to know the extent to which these constraints have adapted to the Nigerian English. This study is based on the same code which is English language but of different varieties such as Nigerian English and English by the native speakers. This research is qualitative in nature, it is based on textual analysis, data were purposively sampled from the reportage columns in some selected Nigerian newspapers such as the interview columns. The theoretical framework used in this study is the Chomskyan Principles and Parameters theory with a focus on movement and bounding theories. Findings show that writers of Nigerian newspaper columns use the subject island, adjunct island and wh-island constraints sparingly and this shows a tactful attempt to avoid expressions which permits long distant wh- movement in order not to violate the subjacency conditions and syntactic constraints. Due to the tactful avoidance, this paper recommends that complex syntactic structures should be thought extensively at all stages in the Nigerian classrooms to enable L2 learners of English gain adequate competence and performance of the language.